Candide and other Stories - Voltaire; Pearson, Roger (Oxford ; New York Oxford University Press, 2006)
"The story of Candide, a naive youth who is conscripted, shipwrecked, robbed, and tortured by the Inquisition without losing his will to live, is accompanied by four other stories"--NoveList.